Thematic Interpretation of Ukhuwwah in the Qur'an and Its Implications for Islamic Character Education - Junaidi; Muhammad Yusuf (Pekerti: Journal Pendidikan Islam dan Budi Pekerti, 2025)
This study explores the concept of ukhuwwah (Islamic brotherhood) in the Qur’an through a thematic interpretation approach to uncover its multidimensional significance in contemporary social contexts. The research aims to understand how the Qur'anic values of ukhuwwah—both Islamiyah and Insaniyah—can foster justice, peace, and inclusivity in a pluralistic society. Using a qualitative methodology, this study collects data from selected Qur’anic verses and interprets them through classical and contemporary exegeses supported by social theories such as social identity and intergroup relations. The analysis reveals five key dimensions of ukhuwwah—spiritual, social, universal, missionary, and struggle-based—that are deeply relevant to addressing modern challenges such as social fragmentation and intergroup conflict. The findings conclude that ukhuwwah in the Qur’an offers theological and practical frameworks for enhancing solidarity and coexistence. This research contributes to the field by offering an interdisciplinary model that integrates Qur’anic studies with contemporary social insights.